2023
DOI: 10.3390/polym15143097
|View full text |Cite
|
Sign up to set email alerts
|

Review of Current Prospects for Using Miscanthus-Based Polymers

Abstract: Carbon neutrality is a requisite for industrial development in modern times. In this paper, we review information on possible applications of polymers from the energy crop Miscanthus in the global industries, and we highlight the life cycle aspects of Miscanthus in detail. We discuss the benefits of Miscanthus cultivation on unoccupied marginal lands as well as the rationale for the capabilities of Miscanthus regarding both soil carbon storage and soil remediation. We also discuss key trends in the processing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…The overview of the world literature on alternative cellulose sources has demonstrated that despite the diversity of Miscanthus species and their habitats [ 47 , 48 , 49 , 50 , 51 , 52 , 53 ], as well as their wide applications ranging from paper industry to biosynthesis products [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ], the information on Miscanthus cellulose as the substrate for chemical functionalization into CN is presently quite limited, except for the authors’ single studies.…”
Section: Introductionmentioning
confidence: 99%
“…The overview of the world literature on alternative cellulose sources has demonstrated that despite the diversity of Miscanthus species and their habitats [ 47 , 48 , 49 , 50 , 51 , 52 , 53 ], as well as their wide applications ranging from paper industry to biosynthesis products [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ], the information on Miscanthus cellulose as the substrate for chemical functionalization into CN is presently quite limited, except for the authors’ single studies.…”
Section: Introductionmentioning
confidence: 99%
“…Miscanthus is a perennial, rhizomatous, tall C4 grass that has been deemed a promising energy crop and is currently being developed to produce lignocellulosic biomass as a sustainable alternative to fossil fuels and as an eco-industrial crop ( Shavyrkina et al., 2023 ). Growing Miscanthus on marginal land for biomass production could contribute to food security and efficient land use ( Xue et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%